2017
DOI: 10.4103/ijo.ijo_437_16
|View full text |Cite
|
Sign up to set email alerts
|

Circumpapillary ganglion cell complex thickness to diagnose glaucoma: A pilot study

Abstract: Purpose:The purpose of this study is to evaluate the applicability of a new optical coherence tomography parameter, the circumpapillary ganglion cell complex (cpGCC) thickness for glaucoma diagnostics.Subjects and Methods:The RS-3000 Advance SD-OCT (NIDEK, Aichi, Japan) was used to measure global and sector macular GCC (mGCC) thickness, circumpapillary retinal nerve fiber layer (cpRNFL) thickness, cpGCC, and circumpapillary total retina (cpTR) thickness in 1 eye of 48 preperimetric/early perimetric primary ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…The 95% prediction intervals describing predicted VF sensitivities were significantly narrower across all cluster-based structure-function models (3.79-4.99 dB) compared with models without clustering applied ( coherence tomography (OCT) technology, high-resolution in vivo visualization of the retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) have become possible, providing invaluable information supplementing the clinical examination of glaucoma. 1,2 Although natural changes to the GCL should not be difficult to capture in theory, various biological factors including concurrent changes due to normal aging and inherent, normal interindividual variation confound our ability to differentiate variations of normal from early disease states. [3][4][5] In conjunction with functional considerations such as variable spatial summation characteristics across different macular regions, [6][7][8] these factors have contributed to so-called discordance in the relationship between macular ganglion cell (GC) measurements and visual field (VF) sensitivity.…”
mentioning
confidence: 99%
“…The 95% prediction intervals describing predicted VF sensitivities were significantly narrower across all cluster-based structure-function models (3.79-4.99 dB) compared with models without clustering applied ( coherence tomography (OCT) technology, high-resolution in vivo visualization of the retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) have become possible, providing invaluable information supplementing the clinical examination of glaucoma. 1,2 Although natural changes to the GCL should not be difficult to capture in theory, various biological factors including concurrent changes due to normal aging and inherent, normal interindividual variation confound our ability to differentiate variations of normal from early disease states. [3][4][5] In conjunction with functional considerations such as variable spatial summation characteristics across different macular regions, [6][7][8] these factors have contributed to so-called discordance in the relationship between macular ganglion cell (GC) measurements and visual field (VF) sensitivity.…”
mentioning
confidence: 99%
“…Our results were not completely unexpected, since cpOR is not influenced by glaucomatous retinal thinning; therefore, no clinically useful correlation was expected from this parameter 1316. It has also been shown that compared with cpRNFL thickness, the most commonly used parameter for glaucoma investigations,1719 cpTR thickness is more reproducible, and cpGCC thickness has higher diagnostic accuracy 9,12. For structure-function relationships, in our current investigation cpGCC thickness and cpTR thickness performed better than cpRNFL thickness, both in terms of the number of significantly correlated sectors and the strength of the correlations in the inferotemporal area.…”
Section: Discussionmentioning
confidence: 43%
“…We found favorable diagnostic performance and strong correlations, particularly in the inferotemporal peripapillary area, which is known to be most severely affected by glaucomatous deterioration. We also found higher diagnostic accuracy for glaucoma using the circumpapillary ganglion cell complex (cpGCC) than with cpRNFL thickness 9. This result suggests that the relationship between cpMP-sensitivity values and cpGCC (a novel parameter) may be stronger than that between cpMP-sensitivity values and cpRNFL thickness (an established parameter).…”
Section: Introductionmentioning
confidence: 66%
“…Later in Oct 2016, Cennamo et al 26 compared patients with different degrees of glaucoma (pre-perimetric, mild, moderate, severe) using SD-OCT and field parameters and concluded that inferior and mean GCC thickness best discriminated between the groups. In May 2017, Kita et al 27 shifted the focus of study in preperimetric glaucoma patients from macular GCC (mGCC) to circumpapillary GCC (cpGCC) using RS-3000 Advance SD-OCT (NIDEK, Aichi, Japan) as the investigating tool and AUROC as comparison variable. They concluded that mGCC was better than cpGCC with respect to diagnostic accuracy but could not comment on its comparison to pRNFL.…”
Section: Discussionmentioning
confidence: 99%